2013
DOI: 10.1074/jbc.m112.430934
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-584 and the Protein Phosphatase and Actin Regulator 1 (PHACTR1), a New Signaling Route through Which Transforming Growth Factor-β Mediates the Migration and Actin Dynamics of Breast Cancer Cells

Abstract: Background: TGF-␤ promotes cell migration in advanced breast cancer. Results: TGF-␤ down-regulates miR-584, leading to a PHACTR1 overexpression, and both are involved in cell migration and actin reorganization. Conclusion:The regulation of miR-584 and regulation of its novel target PHACTR1 are necessary steps for breast cancer cell migration. Significance: MicroRNAs offer an interesting therapeutic target in the treatment of advanced breast malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 78 publications
3
71
0
Order By: Relevance
“…Guled et al [10] reported that the expression level of miR-584 in malignant mesothelioma was higher compared with normal mesothelium, but a functional analysis was not performed in that report. Regulation of miR-584 and regulation of its novel target PHACTR1 were reported as the necessary steps for breast cancer cell migration [1]. And in 2011, a study revealed that miR-584 acts as tumor suppressor by directly targeting the oncogene Rock-1 and decreasing the invasion ability of human clear-cell renal cell carcinoma [6]; this was the first report to show the tumor suppressor functions of miR-584 and the related mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Guled et al [10] reported that the expression level of miR-584 in malignant mesothelioma was higher compared with normal mesothelium, but a functional analysis was not performed in that report. Regulation of miR-584 and regulation of its novel target PHACTR1 were reported as the necessary steps for breast cancer cell migration [1]. And in 2011, a study revealed that miR-584 acts as tumor suppressor by directly targeting the oncogene Rock-1 and decreasing the invasion ability of human clear-cell renal cell carcinoma [6]; this was the first report to show the tumor suppressor functions of miR-584 and the related mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…But little is known on the role of miRNAs in suppressing invasion and migration of TC, let alone their functions and mechanisms of action. It has been reported that the expression of miR-584 can be up-regulated in breast cancer [1], renal clear-cell carcinoma [6], colon cancer [7], rectal cancer [8], myeloid leukemia [9,] and malignant mesothelioma [10,] to suppress the invasion and migration of tumors by targeting PHACTR1 [1], Rock-1 [6], NGX6 [7], etc. Uncovering the target gene of miR-584 to control TC invasion and migration is of central importance in the diagnosis, treatment, and prognosis of TC, and for blocking tumor invasion and migration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown the participation of miRNAs in breast cancer metastasis (Harquail et al, 2012). These studies have shown, for example, that miRlet-7, miR-584, and miR-204 inhibits cell motility by regulating the genes in the actin cytoskeleton pathway, implicating a central role for it in cytoskeletal dynamics (Imam et al, 2012;Fils-Aimé et al, 2013;Hu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise function of PHACTR1 remains unclear, associations with cell migration, motility and invasiveness in tumor tissues have been reported (24). Table III.…”
Section: Discussionmentioning
confidence: 99%